ANALISIS KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH BANK BRI DI MAROANGIN KABUPATEN ENREKANG - Nurrahmah, Andi Citra Indah; Uceng, Andi; Adnan, A.Astinah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the analysis of customer service quality on BRI Bank customer satisfaction in Maroangin, Enrekang Regency. And to find out the factors that influence the quality of BRI Bank customer service in Maroangin, Enrekang Regency. This research method approach uses a quantitative descriptive approach. The population in this study was 101 BRI Bank customers in Maroangin, Enrekang Regency. while the sample in this study was 51 people determined using the Slovin formula. The data collection techniques used in this research were observation, interviews and questionnaires. The collected data was then processed and analyzed using quantitative descriptive analysis techniques with the help of descriptive statistics using SPSS and a Likert scale. The results of this research indicate that BRI Bank customer service in Maroangin, Enrekang Regency is categorized as good. The results of this research show that the average percentage value of the five BRI Bank customer service quality indicators is 74.2% in the good category. The average value of customer satisfaction is 74.9% in the good category. Factors that influence the quality of BRI Bank customer service with an average percentage value of 64% with a good category where human resources with a value of 76.3%, awareness of rules 58%, organization 41.5%, skills and abilities 68% , service facilities 73% and customer experience 66%.